Estado de esfuerzos estáticos en la interface de placas Coco-Caribe en Costa Rica: Interpretación mecánica para el origen de asperezas en la zona sismogénica - Lücke, Oscar H. (2015)
The forearc region along the Central American Subduction Zone shows a series of trench-parallel positive gravity anomalies with corresponding gravity lows along the trench and toward the coast. These features extend from Guatemala to northern Nicaragua. However, the Costa Rican section of the forearc does not follow this pattern due to the segmentation of the along-trench gravity low, the absence of the coastal low, and the presence of emerged continental mass along the forearc gravity high at the Nicoya Peninsula. Geodetic and seismological studies along the Costa Rican Subduction Zone suggest the presence of coupled areas in the seismogenic zone beneath the Nicoya Peninsula prior to the 7.6 Mw magnitude earthquake in September 5th, 2012. These areas have previously been associated with asperities. Based on the structure of the overriding plate, former publications have proposed a mechanical model for the origin of asperities along the Chilean convergent margin, in which the dense igneous material in the forearc of the overriding plate above the seismogenic zone modifies/disturbs the state of static stress and influences seismogenic processes. In Costa Rica, surface geology and gravity data indicate the existence of dense basalt/gabbro crust overlying the seismogenic zone where the coupling is present. Bouguer anomaly values in this region reach up to 120×10-5 m/s2 and are the highest for Costa Rica. In this research, the state of static stress on the Cocos-Caribbean plate interface is calculated based on the geometry and on the density distribution of a 3D litosphere density model of the subduction zone as interpreted from gravity data from combined geopotential models. Results show a spatial correlation between the coupled areas at the Nicoya Peninsula and the presence of anomalies on the static state of stress on the plate interface. The stress anomalies were calculated for the normal component of the vertical stress on the seismogenic zone and were interpreted as being generated by the dense material which makes up the forearc in the area. The dense material of the Nicoya Complex mafic rocks and the topographic load of the peninsula on the seismogenic zone lay a role in the distribution of coupled areas and the seismic behavior of the region, since the anomalies on the normal stress on the plate interface may increase the shear stress threshold to generate the rupture.